SHEDDING DETECTION OF NEWCASTLE DISEASE VIRUS VACCINE IN LAYING HENS POST-VACCINATION - Dewi, Ni Kadek Kamala; Kencana, Gusti Ayu Yuniati; Suardana, Ida Bagus Kade (Buletin Veteriner Udayana, 2024)
The poultry industry in Indonesia is still experiencing problems, especially in terms of disease attacks, one of which is Newcastle Disease (ND). ND is caused by Avian Paramyxovirus type-1 (APMV-1) virus and is an infectious and also acute disease in Indonesia. ND management has so far been carried out by vaccination and improved husbandry management. ND vaccination can use active vaccines, inactive vaccines or combination vaccines. Despite vaccination, ND is still frequently reported. The aim of this study was to determine the safety of Newcastle Disease (ND) Genotype VII vaccine based on post-vaccination virus shedding. Shedding viruses leave the body of poultry through excretion, especially feces, which can cause environmental pollution. The samples used were 10 cloacal swab samples of laying hens taken for five periods and isolation of embryonated chicken eggs. The inoculated liquid on embryonated chicken eggs was harvested and HA test was conducted to check the shedding of ND vaccine virus. The results showed no shedding of the vaccine virus characterized by negative results in the HA test. These negative results indicate that the inactivated ND Genotype VII vaccine is safe for the environment, however farmers need to implement biosecurity to prevent the entry of ND into the farm.